2011
DOI: 10.1080/01431161.2010.512947
|View full text |Cite
|
Sign up to set email alerts
|

A current review of empirical procedures of remote sensing in inland and near-coastal transitional waters

Abstract: The empirical approach of remote sensing has a proven capability to provide timely and accurate information on inland and near-coastal transitional waters. This article gives a thorough review of empirical algorithms for quantitatively estimating a variety of parameters from space-borne, airborne and in situ remote sensors in inland and transitional waters, including chlorophyll-a, total suspended solids, Secchi disk depth (z SD ), turbidity, absorption by coloured dissolved organic matter (a CDOM ) and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
253
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(271 citation statements)
references
References 150 publications
(229 reference statements)
2
253
0
16
Order By: Relevance
“…Various remote sensing algorithms have been suggested to measure Chla and turbidity (or TSS) for inland waters with complex optical properties [17]. For example, the effectiveness of the following 2-band model (2-BM; hereinafter referred to as a C1 model) as a Chla algorithm has been shown using the red and near-infrared bands [18,19].…”
Section: Chlorophyll-a and Turbidity Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various remote sensing algorithms have been suggested to measure Chla and turbidity (or TSS) for inland waters with complex optical properties [17]. For example, the effectiveness of the following 2-band model (2-BM; hereinafter referred to as a C1 model) as a Chla algorithm has been shown using the red and near-infrared bands [18,19].…”
Section: Chlorophyll-a and Turbidity Algorithmsmentioning
confidence: 99%
“…Moreover, the current situation cannot be dealt with using conventional point source monitoring; thus, it is vital to establish technology such as remote sensing that can simultaneously monitor wide areas. Conventional water quality remote sensing relies mainly on algorithms dealing with blue and green light, but in optically-complex inland waters, the red and near-infrared parts of the spectrum are often used [17]. For example, methods such as two-band algorithms [18,19], three-band algorithms [20,21] and four-band algorithms [22,23] have been proposed to measure chlorophyll-a (Chla).…”
Section: Introductionmentioning
confidence: 99%
“…Earth observation provides a synoptic view of systems that cannot be replicated through field-based sampling and one that can be obtained at relatively high temporal frequencies to build long-term observational records of environmental change. However, many previous studies have shown that the performance of in-waters models for the retrieval of physical and biogeochemical parameters from Earth observation data can vary tremendously between water bodies with very different optical properties and overlying atmospheres (Guanter et al, 2010;Matthews et al 2011). The Danube basin and its diversity of water bodies from the large, deep clear water lakes to the south of the Black Forest to the highly turbid environments of the coastal lagoons and waters of the Black Sea will undoubtedly pose a challenge for the operational monitoring of water quality from satellites.…”
Section: Special Issue Science Of the Total Environmentmentioning
confidence: 99%
“…Most algorithms for the estimation of Secchi depth take advantage of the bands in red because as water clarity decreases, the water-leaving radiative signal in the red spectrum usually increases (Matthews, 2011). The retrieval of Secchi depth can also be achieved successfully using relatively broad spectral bands and thus many studies have capitalized on Landsat-MSS/-TM/-ETM+/-OLI data as they offer high spatial resolution ( There are also a relatively large number of studies dedicated to the retrieval of TSM in inland waters, using sensors ranging from Landsat-TM/ETM+/OLI to ocean colour sensors such as MERIS and MODIS.…”
Section: Special Issue Science Of the Total Environmentmentioning
confidence: 99%
See 1 more Smart Citation